KONSENTRASI LARUTAN GULA DAN EFEKTIF MIKROORGANISME TERHADAP KUALITAS PUPUK ORGANIK CAIR SAMPAH PASAR - Bayu Handoko; Bagus Nur Rochman; Ari Kurniawati (Unit Penelitian dan Pengabdian Masyarakat (UP2M) Politeknik Banjarnegara, 2020)
Market waste in urban areas is a problem that needs to be solved so that it does not become a big issue in the community. One of them is by making it as liquid organic fertilizer. The purpose of this study was to determine the concentration of the sugar solution, the effective concentration of microorganism, and the proper interaction in breaking down market waste into high quality liquid organic fertilizer. The design of the study used a completely randomized design (CRD) with three replications. The factors tested were effective concentrations of microorganisms 1.0% (M1), 1.5% (M2), 2.0% (M3) and concentrations of sugar solutions 10% (G1), 15 (G2), 20% (G3). The combination of treatments obtained as many as 9 treatment combinations, so that the total experimental units amounted to 27 experimental units. The right sugar solution in breaking down market waste into liquid organic fertilizer is a solution of sugar 10% (G1) to pH and solution of sugar 30% (G3) to EC and Temperature. Sugar solutions and effective microorganism solutions are appropriate in decomposing market waste into liquid organic fertilizers are 30% sugar solution (G3) and 2.0% effective microorganism solution (M3). Interaction between sugar solution concentration and effective microorganisms does not occur significantly because the amount of sugar solution given has not been able to significantly increase the microorganism population. Kata kunci: efektif mikrorganisme, larutan gula, pupuk organik cair Abstrak Sampah pasar di perkotaan merupakan permasalahan yang perlu dipecahkan agar tidak menjadi isu besar di masyarakat. Salah satunya dengan cara menjadikannya sebagai pupuk organik cair. Tujuan dari penelitian ini adalah untuk mengetahui konsentrasi larutan gula, konsentrasi larutan efektif mikroorganisme, dan interaksinya yang tepat dalam menguraikan sampah pasar menjadi pupuk organik cair yang berkualitas. Rancangan peneitian menggunakan rancangan acak lengkap (RAL) dengan tiga kali ulangan. Faktor yang dicoba adalah konsentrasi efektif mikroorganisme 1,0 % (M1), 1,5 % (M2), 2,0 % (M3) dan konsentrasi larutan gula 10 % (G1), 15 % (G2), 20 % (G3). Kombinasi perlakuan yang diperoleh sebanyak 9 kombinasi perlakuan, sehingga unit percobaan keseluruhan berjumlah 27 unit percobaan. Larutan gula dan larutan efektif mikroorganisme yang tepat dalam menguraikan sampah pasar menjadi pupuk organik cair adalah larutan gula 30% (G3) dan larutan efektif mikroorganisme 2,0 % (M3). Interaksi antara konsentrasi larutan gula dan efektif mikroorganisme tidak menunjukkan interaksi yang nyata karena banyaknya jumlah larutan gula yang diberikan pada semua perlakuan belum dapat meningkatkan jumlah mikroorganisme dengan signifikan.